Intervening Opportunities and Competing Migrants in Turkish migration to Germany, 1969-2008 - Akkoyunlu, Sule (Migration Letters, 2012)
This study defines, specifies and empirically tests the concept of intervening opportunities proposed by Stouffer (1940) and the theory of competing migrants proposed again Stouffer (1960) in the context of international migration. An empirical model of Turkish migration to Germany is developed and tested for the 1969-2008 period, using the cointegration technique. We find strong evidence of intervening opportunities and competing migrants. Although, competing migrants are significant in the short as well as in the long-run, intervening opportunities are only significant in the short-run. The results have an important policy implication for the Turkey’s accession to European Union. Thus, the migration pressure from Turkey with the accession can be managed by increasing intervening opportunities, hereby increasing foreign direct investments and altering the demand for competing migrants.